PENGEMBANGAN KLUB BACA UNTUK AREMA DI TPQ NURUL IMAN DESA TIRTOMOYO KEC. AMPELGADING - Efendiy, Khoirul; Umamy, Etty; Kristiawan, Indria; Perdana, Sukma (ABIDUMASY, 2026)
Low reading interest among children and adolescents in nonformal religious education institutions remains a challenge in strengthening basic literacy. This condition was also identified among students of TPQ Nurul Iman in Tirtomoyo Village, Ampelgading District, where access to reading materials is limited and structured literacy activities are not yet available. This community service program aimed to develop the Children and Adolescents Reading Club (ARema) as a community-based literacy strengthening initiative within the TPQ environment. The program was implemented from May to July 2024 and involved TPQ administrators, teachers, and students. The implementation stages included needs assessment, literacy awareness sessions for administrators, improvement of the reading space and book collection, regular group reading activities, and continuous mentoring and evaluation. The novelty of this program lies in the integration of literacy space development, scheduled reading club management, and collaborative reading activities accompanied by simple discussions and retelling exercises. The results indicate increased student participation in reading activities, reflected in consistent attendance in reading club meetings, a higher number of completed readings, and improved ability to understand and retell reading materials. These findings demonstrate that community-based reading clubs can serve as an effective approach to strengthening literacy culture within nonformal educational settings. Keywords: reading club, literacy, TPQ, community service